La inclusión: un reto para el sistema educativo costarricense - Quijano Chacón, Grettel (2008)
This article it written in reference to a series of aspects related to the educative inclusion, in order to make conscience in the educative community and the Costa Rican society, about the importance of taking into practices attitudes of respect, tolerance and solidarity towards the students with special educative necessities associated to intellectual disability, which seeks the construction of a fair and equitable society. For inclusion to be a reality it is necessary that a shared responsibility exists in which each one assumes its responsibilities with the purpose of improving the quality of life of this population.